Gaming among female adolescents: profiling and psychopathological characteristics in the Indian context - Thakur, Pranjali Chakraborty; Sharma, Manoj Kumar; Mohan, Vineeth; Kommu, John Vijay Sagar; Anand, Nitin; Marimuthu, Palaniappan (Frontiers in Psychiatry, 2023)
Objectives: Gaming is a predominant leisure time activity among adolescents and research literature suggests that unrestrained gaming behavior might end up in gaming disorder. Both ICD-11 & DSM-5 have recognized gaming disorder as a psychiatric condition and grouped it under the category of behavioral addiction. Research on gaming behavior and addiction are largely based on data from male population and problematic gaming has largely been understood from male perspective. In this study, we are attempting to bridge the existing lacuna in literature by exploring gaming behavior, gaming disorder, and its related psychopathological characteristics among female adolescents in India. Methods: The study was conducted on a sample of 707 female adolescent participants who were contacted through schools and academic institutes using multi-stage sampling. The study adopted cross-sectional survey design and data was administered using mixed modality of online and offline data collection. The participants filled the following set of questionnaires: Socio-demographic sheet, Internet Gaming Disorder Scale – Short-Form (IGDS9-SF), Strength and Difficulties Questionnaire (SDQ), Rosenberg self-esteem scale and Brief sensation seeking scale (BSSS-8). The data gathered from the participants were then statistically analyzed using SPSS software. Results: The descriptive statistics revealed that 0.8% of the sample (i.e., 5 participants out of 707) obtained scores meeting gaming addiction criteria. Correlation analysis demonstrated significant relationship of all the psychological variables with total IGD scale scores. Total SDQ, total BSSS-8, domain scores of SDQ: emotional symptoms, conduct, hyper-activity & peer problems were positively correlated whereas Total Rosenberg scores and domain score of prosocial behavior of SDQ were negatively correlated. Man- Whitney U test was employed to compare the ‘addicted’ & ‘non-addicted’ female participants, which revealed significant difference among the groups on Emotional symptoms, conduct, hyperactivity/ inattention, peer- problem and self-esteem scale scores. Further, quantile regression was computed and it showed that conduct, peer-problem, and self-esteem displayed trend level prediction for gaming disorder. Conclusion: Female adolescents who are prone towards gaming addiction can be identified through the psychopathological characteristics of conduct, peer-problem and low self-esteem. This understanding can be useful in developing a theoretical model focusing on early-screening and preventive strategies for at-risk female adolescents